PREVALENCE OF CAESAREAN SECTION NICHE IN WOMEN WITH PREVIOUS CAESAREAN SECTION AND ITS EFFECT ON REPRODUCTIVE HEALTH - Rahim, Gona Aziz (Journal of Sulaimani Medical College, 2025)
Background The Cesarean Section (CS) rate has been increasing in recent practice worldwide as well as in Iraq, and there are many gynecological and obstetric problems related to CS also increasing in parallel to CS, some of them may be related to cesarean scar niche (CSN). There has yet to be a consensus about the gold standard method for diagnosing CSN, its prevalence, and the symptoms it causes. Objective This study aims to fi nd the prevalence of CSN in women with previous CS and how common gynaecological symptoms, including abnormal uterine bleeding, are among women who have had cesarean section niches compared to women with no CSN. Patients and Methods This is a cross-sectional study conducted in private clinics of gynaecology and ultrasonography in Sulaymaniyah/ Kurdistan/Iraq from December 2020 to May 2023. It involved 259 women with a history of previous Cesarean section for whom transvaginal ultrasound was done to fi nd the presence or absence of CSN. Accordingly, they divided into two groups: the fi rst with CSN and the second with no CSN. Both groups followed prospectively for several parameters: postmenstrual spotting, intermenstrual bleeding, dysmenorrhea, dyspareunia, chronic pelvic pain, and subfertility—the chi-square test used for statistical analysis of the variables. Results This study was carried out on 259 women with a history of one or more CS. Diagnosis of CSN done by 2D TVU: 44% of them had CSN, and 66% had no CSN; the prevalence of CSN was higher in women with repeated CS (P˂0.001). Not all scar niches had symptoms but were frequently symptomatic; in this group, 50.9% were symptomatic, while in those with no CSN, 26.2% were symptomatic (P˂0.001). Postmenstrual spotting and dysmenorrhea were the most predominant symptoms, which were statistically signifi cant compared to the group of no niche (P P˂0.001). At the same time, dyspareunia, chronic pelvic pain, and subfertility were not signifi cantly increased. In the group of CSN, 44.73% had large, and 55.26% had small niches. Postmenstrual spotting and dysmenorrhea symptoms were more prevalent in women with large CSN than in small CSN (P˂0.001). Conclusion The prevalence of cesarean scar niche was 44% in women with previous CS, which can cause postmenstrual spotting and dysmenorrhea. More studies need to be addressed regarding intermenstrual bleeding, dyspareunia, chronic pelvic pain, and subfertility. Therefore, the practice of cesarean section on request is not recommended.
Keywords: Caesarean section; Caesarean scar niche; Transvaginal ultrasound; Postmenstrual spotting,dysmenorrhea